Introducing syntax - Koeneman, Olaf; Zeijlstra, Hedzer Hugo 1975- (Cambridge University Press, 2017)
"Syntax is the study of how sentences are built. Whereas the grammar of English (or other languages) might look like a rather chaotic set of arbitrary patterns, linguistic science has revealed that these patterns can actually be understood as a result of a small number of grammatical principles. This lively introductory textbook is designed for undergraduate students in linguistics, English and modern languages with relatively little background in the subject, offering the necessary tools for the analysis of phrases and sentences, while at the same time introducing state-of-the-art syntactic theory, in an accessible and engaging way. Guiding students through a variety of intriguing puzzles, striking facts and novel ideas, Introducing Syntax presents contemporary insights behind syntactic theory in one clear and coherent narrative, avoiding unnecessary technical detail and enabling readers to understand the rationale behind technicalities. Learning features include highlighted key terms, further reading suggestions and numerous exercises and activities throughout, placing syntax in a broader grammatical perspective"--Provided by publisher.